Mask use in the community setting around the world during the COVID-19 pandemic. Efficacy, benefits, and risks: a review (Revista de Medicina Clinica, 2021)
Abstract: With the emergence of SARS-CoV-2 in Wuhan (China) towards the end of 2019, the world has faced a new pandemic, which so far already exceeds 5 million infected, called COVID-19. In the absence of an effective treatment against the infection, public health measures have obtained great relevance for the containment of the virus. These include hand washing and social distancing. The widespread use of face masks in the community setting has been a public health measure that, until now, has not been fully adopted by the international community due to the limited scientific evidence available. This review presents the current scientific evidence regarding the efficacy of this measure to mitigate the spread of this and other pandemics. As well as the benefits and risks that emanate from it.Keywords: SARS-CoV-2, COVID-19, Mask use
Keywords: SARS-CoV-2; COVID-19; Mask use